#### Answer

$6(x-2)(x+1)$

#### Work Step by Step

Factor out $6$ to obtain:
$=6(x^2-x-2)$
The leading coefficient of the trinomial is 1.
Factor the trinomial by looking for the factors of the constant term $(-2)$ whose sum is equal to the coefficient of the middle term $(-1)$.
Note that $-2=-2(1)$ and $-2+1 = -1$.
Thus, the factors we are looking for are $-2$ and $1$.
This means that the factors of the trinomial are: $x-2$ and $x+1$
Therefore the completely factored form of the given polynomial is:
$=6(x-2)(x+1)$